Distance formative process in Food Security and Nutrition in the Community of Portuguese Speaking Countries: building educational practices (abstract: p. 17) - Galesi-Pacheco, Lilian Fernanda [UNESP]; Perinelli Neto, Humberto [UNESP] (FapUNIFESP (SciELO), 2023)
Formative processes to strengthen Food Security and Nutrition (FSN) are demanded by the Community of Portuguese Speaking Countries (CPLP). Our objective was to describe and analyze the educational practices developed by teachers, aiming to reflect and propose adjustments to improve the distance formative process in FSN in the CPLP context (Brazil, Cape Verde, Mozambique and São Tomé and Príncipe). This is applied research, with a qualitative approach and a descriptive and explanatory nature, using video classes as study material, mainly based on Discursive Textual Analysis. The proposal indicates that courses of the same nature require: teacher education; recognition of students’ knowledge; insertion of dialogue in the video lessons; offering local activities capable of generating an understanding of the reality; creation of a sequence for the elaboration of the undergraduate thesis (UT); and writing UTs aimed at transforming reality.
Proceso formativo a distancia en Seguridad Alimentaria y Nutricional en la Comunidad de los Países de Lengua Portuguesa: construcción de prácticas educativas (resumen: p. 17)
Processo formativo a distância em Segurança Alimentar e Nutricional na Comunidade dos Países de Língua Portuguesa: construindo práticas educativas
Keywords: Community of portuguese speaking countries; Distance education; Educational practices; Food security and nutrition